GAMBARAN PENETRASI SEMEN IONOMER KACA KE DALAM DENTIN GIGI SULUNG DENGAN DAN TANPA KONDISIONER (Evaluasi Scanning Electron Microscopy) - Darnus Darnus; Ismu Suharsono Suwelo; Hendrarlin Soenawan (Faculty of Dentistry, Universitas Indonesia, 2015)
The objective of this research was to know the difference between the penetration of glass ionomer cement (Chemflex, Dentsply) in dentin of primary teeth with and without conditoner (10% polyacrylic acid). THe primary molar tooth which were observed by Scanning Electron Microscopy (SEM) 100x magnitude ws measured for the length of glass ionomer cement penetration in dentin of primary tooth with and without conditioner. The t test showed that there was no significant difference between the length of glass ionomer cement penetration in dentin of primery teeth with and without conditioner.